Strengthening the International Seabed Authority's knowledge-base: Addressing uncertainties to enhance decision-making. (April 2020) - Ginzky, Harald; Singh, Pradeep A.; Markus, Till
Abstract: This article argues that the process of developing the regulations of commercial deep seabed mining operations presents a window of opportunity to actively and systematically address existing uncertainties regarding the environmental effects of seabed mining activities. To this end, the developing process of regulations could, for example, enable the ISA to actively engage in generating and synthesizing information, make it publicly available for scrutiny, and consequentially apply this gained body of knowledge to its decision-making procedures at all relevant stages. Here, we assess to what extent international law and existing policy support the practice such a proactive knowledge management system. Premised on this, we suggest some potential measures and institutional adjustments that would help spur the effort to strategically target and fill knowledge gaps. We aver that these adjustments, if implemented together, would substantially enable the ISA to increase the quality and legitimacy of its outputs, and thus, to meet its legal and political responsibilities.